Russia And Germany: Search For A New Model Of Neo-Industrial Social State - Andreyeva, Yelena Leonidovna; Date, Marion; Ratner, Artem Vitalyevich (Economy of Regions, 2015)
Russia and Germany are traditionally reputed as countries with socially oriented economies. Namely, these countries are also close by the index of the share of real sector of economy at GDP. And however, Germany is a founder of social market household largely defined its leadership in world economy, in current conditions of crisis of “the state of general welfare” the search of a new model of development for Germany is also important as for Russia stood on the way of modernization and neo-industrialization. In the article, the hypothesis about forming of the new model of development uniting the social orientation of economy, processes of neoindustrialization, and globalization is made. At the same time, the social orientation is the main aim of socio-economic development, neo-industrialization is a way to achieve it, and globalization is a criterion presupposing more effective use of resources. Theoretical backgrounds of development of “social state” are generalized in the works of German and Russian classics put the backgrounds of economic humanism, it has allowed to prove the fatality of modernization process without considering of deep mental backgrounds and civilization codes of the nation development. The methodological approaches to development of a new model of neo-industrial social state with emphasizing different levels: global, national, local, individual are worked out; and the technique for estimation of factors and conditions of its development is proposed. The technique is tested on the example of Russia and Germany, The comparative analysis conducted has allowed to make the conclusion about similarity of target guidelines, initial conditions, problems and ways of their solving in these countries, that is to be considered both in a strategy and a policy of socio-economic development of these countries and by their international partnership.